Basement Configuration of the Tomini Basin deduced from Marine Magnetic Interpretation - Kusnida, Dida; Subarsyah, Subarsyah; Nirwana, B. (Indonesian Journal on Geoscience, 2009)
DOI:Â 10.17014/ijog.v4i4.86This paper presents the result of marine magnetic survey in Tomini Basin, Central Indonesia. On the basis of marine magnetic modeling, the main structural and geological elements of the basement of Tomini Basin are identified. At the centre of the basin, the up-doming feature points to an elevated magnetic susceptibility value. A geological model indicates that the entire basement of Tomini Basin is characterized by an oceanic-like crust with a basin axis at the centre nearly an east-west direction and suggests a rift-related graben.